In Vitro Antiplasmodial Activity And Stage-Specificity Of 1,10-Phenantroline Derivatives On Plasmodium Falciparum Cycles - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Mustafa In Vitro antiplasmodial activity and stage-specificity of 1,10-phonantroline derivatives on Plasmodium falciparuns cycles Background : The study of in vitro antiplasmodial activity of diazaâ¢analogs of phenanthrene leads to retain the 1,10-phananthroline skeleton as a potential antimalarial leader molecule. On the basis of the skeleton, a new series of 1.10-ohonanthroline derivatives have been synthesized. Objective To evaluate the in vitro antiplasmodial activity and cytotoxicity of seven now 1,10-phenantroline derivatives, Methods : The in vitro antiplasmodial activity was tested on throe strains of Plasmodium felciperom. FcB1-Columbia, FcM29 chloroquine resistant and a nigerian chloroquine-sensitive strains while their cytotoxicity was tested on human fibroblast cell lines. The parasite or cell growth was estimated by I'1-]â¢ hipoxanthine incorporation alter 24 and 72 hours incubation with each molecule tested. A control of parasite or cell frood from any molecules was referred to as 100% growth. For this radioactive method, value showing the concentration inhibiting 50% of the parasite growth was determined by probil analysis. Specific activity of the most active molecules on different stage of R falciparum was also evaluated, Results : The results showed that the ICI, values of 1,10-phenanthroline derivatives ranged from 0.02 to 2,4 mM un the chlotoquine resistant strains 1Fc(31-Columbia and FcM29 strains, and from 0.14 to 2.4 mM on the chloroquine-sensitive strain Inigerian strain]. Two molecules, 7.chloro-8-12-chloro-ethyl)-1,9-climethyl(1,10)-phenanthrolin-1-lorn iodide 7-chloro-B-12-chlono-ethyl)-1-uttiyi-9-methykl,10-phenanthrolinâ¢ 1-ium iodide (31 exhibited the best in vitro antiplasmodial activity with an ICso value ranging 0,02 to 0.16 mM. These two molecules also had higher Cytotoxicity Index (C11 then other molecules tested with a CI value ranged between 79.0 and 242.7. In addition, these molecules interacted particularly during the 16," and the 40'n hour intervals of the plasmodium cycle. Conclusion : Thu molecules 12) and (3) were the most active molecules against three P. falciparum strains tested with low toxicity, In addition, these molecules acted during the growing trophozoite and mature schizont stages of the plasmodium cycle.